2012
DOI: 10.1155/2012/875310
|View full text |Cite
|
Sign up to set email alerts
|

A Note on Child Policy and Fertility in an Overlapping Generations Small Open Economy: When the Labour Market Institutions Matter

Abstract: We examine how fertility reacts to the public provision of child allowances in a small open economy with overlapping generations. When the labour market is competitive, we find that a child allowance policy acts as a fertility-enhancing device. In contrast, when the labour market is unionised the child policy may be ineffective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Moreover, in the next section, we check the robustness of the result that an increase of longevity increases fertility, by introducing a family policy rather widespread in developed countries for fighting against the dramatic fertility drop: a per child cash subsidy policy. 16…”
Section: Social Security Longevity and Fertilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in the next section, we check the robustness of the result that an increase of longevity increases fertility, by introducing a family policy rather widespread in developed countries for fighting against the dramatic fertility drop: a per child cash subsidy policy. 16…”
Section: Social Security Longevity and Fertilitymentioning
confidence: 99%
“…As to the issue of the relationship between pension systems and low fertility in Europe, see, for instance, Cigno and Werding [15]. 16. Child policies have been investigated, although in a different context, for instance, by Fanti and Gori [8,16].…”
Section: International Journal Of Population Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Fanti and Gori (2007) showed that for any given minimum (or union"s) wage value, the child subsidy reduces capital accumulation and increases unemployment, and ultimately decreases demand to bear children in a closed economy. Fanti and Gori (2012) examined the effect of child allowances on fertility in a small open economy, and find that in the context of competitive labor market, it acts as a fertility-enhancing device, while in a unionized market the child policy may be ineffective. But both of them failed to suggest how to increase fertility and decrease unemployment by using child policy.…”
Section: Introductionmentioning
confidence: 99%